Fourier analysis of the RELAP5/3D adaptive time-stepping scheme on a natural circulation loop. (March 2018) - Braz Filho, Francisco A.; Ribeiro, Guilherme B.; Caldeira, Alexandre D.
Highlights: Four maximum time-step sizes were assessed for a transient simulation with RELAP5/3D. A two-phase natural circulation loop was analyzed. An experimental facility was used for comparison purposes. In order to evaluate two-phase instabilities, FFT and RMSD analyses were performed. The maximum time-step size of 10 −2  s promoted the greatest agreement. Abstract: The use of natural convection as a passive heat removal mechanism has been widely explored as a safety system of nuclear power plants. Characteristics like low complexity and economy makes Natural Circulation Loop (NCL) an encouraging technology which is being investigated for the Generation IV nuclear energy systems. As a manner to enhance the performance prediction of NCL, this study provides an evaluation of the adaptive time-stepping scheme that the RELAP5/3D code uses to calculate the time-step size applied during a transient simulation. Additionally, the Fast Fourier Transform (FFT) and the Root-Mean-Square Deviation (RMSD) procedures were conducted in order to investigate the agreement between the numerical and experimental data during the time frame when two-phase flow instabilities appear. Temperature measurements extracted from an experimental facility were used as the baseline data. For this evaluation, four different maximum time-step sizes were considered and their effect on the prediction of NCL temperatures was analyzed.